Perkawinan Tradisi Jujuran dalam Adat Bugis Perantau di Kutai Kartangera: Suatu Kajian Perbandingan dengan Hukum Islam - Eko Rial Nugroho; Abdul Wahid (Wajah Hukum, 2019)
One of the marriage processions is the presence of dowry. The culture of giving dowry differs from one region to another. The practice of the jujuran tradition in Kuala Samboja Village, Samboja District, Kutai Kartanegara District has social impacts, including men feeling restrained to get married. Whereas Islam provides convenience, so that each can enjoy a halal and good relationship. The problem is how is the comparison between marriage with the jujuran tradition in the Bugis nomads in Kutai Kartanegara with marriage in Islamic Law. The research method is a normative legal research that bases its analysis on legislation related to the research problems studied. The approach in this study is a doctrinal approach. Sources of research data are secondary data, namely data obtained from library research in the form of legal materials consisting of primary legal materials, secondary legal materials, tertiary legal materials. The results of the study, first, the jujuran tradition is a unity in the traditional marriage procession of the community of Kuala Samboja Village, Samboja District, Kutai Kartanegara Regency. The jujuran tradition is one of the benchmarks for the sustainability of marriage plans. The principle of marriage in the jujuran tradition is that marriage will not be carried out or canceled, if the jujuran cannot be fulfilled by the prospective bridegroom and his family. Secondly, marriage in Islam must fulfill the terms and conditions of marriage. The marriage guardian is one of the important elements in a marriage contract because marriage will no longer valid if it is done without guardian. There has been event that a marriage guardian refusing to marry his daughter on the grounds of contradicting the syara’, a reason that are not justified by the law of shara 'which is referred to as adhal (reluctant) then there must be replaced by wali hakim. The position of the wali hakim in the process of the marriage as the guardian in lieu of the guardian of the prospective bride or replacing the position of the nashab guardian who, due to certain circumstances, cannot or does not want to become a marriage guardian for his daughter. The position and authority of the judge's guardian is the same as the nashab guardian or guardian of the bride lady who is under his guardianship.